Pendekatan dan Tantangan Dalam Menejemen Pendidikan Islam di SDIT Adzkia - Hilwa Ismi Fadia; Salma Vasya Aulia; Adisti Nurfatimah; Abdul Halim; Adi Rosadi (An Nafi': Multidisciplinary Science, 2024)
Islamic education at SDIT Adzkia faces unique approaches and challenges in its management. This paper describes research methods which include data collection through interviews and documentation as well as qualitative data analysis. The research results highlight a management approach that includes character building, strengthening the content of the Koran, and improving the quality of worship. SDIT Adzkia uses the strategy of teachers as role models, integrating Islamic values ​​in the curriculum, involving the community, and utilizing technology. Additionally, schools face limited resources with staff development programs and curriculum adjustments. SDIT Adzkia also ensures that Islamic values ​​are implemented in students' daily lives through daily muthaba'ah practices. In conclusion, the school aims to provide Islamic education that is relevant to the demands of the times while maintaining a strong Islamic identity.